2014
DOI: 10.2175/106143014x14062131178312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short‐term Exposure of Selected Aromatic Nitrogen Compounds on Wastewater Treatment

Abstract: The biodegradation of melamine and p-nitrophenol (PNP) and their impact on wastewater treatment was evaluated after a short-term individual chemical loading in activated sludge treatment systems. Melamine was not degraded and quickly washed out of the system. PNP was degraded, but it led to a prolonged period of nitrification inhibition and deterioration of effluent quality. Both melamine and PNP loadings increased the effluent nitrogen concentrations, with their main contributors being melamine and NH 4 þ , r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Zuriaga-Agustí et al [10] also demonstrated that low pNP concentration (25 mg/L) had no adverse effect on activated sludge process, whereas 125 mg/L pNP decreased sludge's activity by 29%. Guo et al [19] reported that addition of pNP as metabolic uncoupler could be easily degraded at reasonable concentrations, although even a small amount of such uncoupler can reduce biomass production. Moreover, Inglezakis et al [20] stated that 8.5 mg/L pNP resulted in low oxygen uptake rate inhibition (<20%).…”
Section: Introductionmentioning
confidence: 99%
“…Zuriaga-Agustí et al [10] also demonstrated that low pNP concentration (25 mg/L) had no adverse effect on activated sludge process, whereas 125 mg/L pNP decreased sludge's activity by 29%. Guo et al [19] reported that addition of pNP as metabolic uncoupler could be easily degraded at reasonable concentrations, although even a small amount of such uncoupler can reduce biomass production. Moreover, Inglezakis et al [20] stated that 8.5 mg/L pNP resulted in low oxygen uptake rate inhibition (<20%).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, a few enriched cultures have been available for some branches of Thaumacheota, for example Nitrosopumilus For wastewater treatment plant (WWTP) field of study, AOA was found for the first time in activated sludge bioreactors in the USA by Park et al (2006). During 2006-2017, AOA was found in WWTPs in many worldwide countries; for example, the USA (Wells et al 2009) Hong Kong (Jin et al 2010;Ye and Zhang 2011;Zhang et al 2009) Thailand (Limpiyakorn et al 2011;Sonthiphand and Limpiyakorn 2011),Turkey (Yapsakli et al 2011), China (Bai et al 2012;Gao et al 2013;Guo et al 2014;Zhang et al 2009;Zhang et al 2015), Singapore (Zhang et al 2009) (Sauder et al 2017;Shen et al 2013;Tourna et al 2011). Some compounds act as a scavenger of nitric oxide (NO) such as 2-phenyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO) (Shen et al 2013).…”
Section: Aoamentioning
confidence: 99%
“…Since, PNP has been reported as priority pollutant by United States Environmental Protection Agency ( USEPA) . PNP is able to cause teratogenic, carcinogenic, and mutagenic to organisms (Guo et al 2014). Therefore, U.S.EPA listed PNP as a considering pollutant and restricted the concentration of PNP in natural water to be less than 10 ngL -1 .…”
Section: Aoamentioning
confidence: 99%
See 2 more Smart Citations